2020
DOI: 10.21093/mj.v19i1.2055
|View full text |Cite
|
Sign up to set email alerts
|

Deterring or Entertaining? Can the Caning Punishment Execution in Aceh Meet its Objective?

Abstract: This article probes whether the implementation of the caning sentence in Aceh may reach its objective of deterrent effect given the way the execution conducted. From the field observation, the flogging was not much different from entertainment. The mass gathered in one place to watch the execution; they include children, street vendors, researchers, and journalists. There was a stage, VIP seats for guests, loudspeakers, administrative arrangements, and the caning punishment procession. Using a qualitative rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Subsequently, the execution of caning sentence for this case was performed to provide educational media for the society that views the execution. In contrast, a study has reported that although the local government of Aceh intended to implement the Islamic Sharia in to achieve a well-behaved society, the people who view the caning execution perceived it more as entertainment [11], rather than educational or deterring. Our assumption might have confirmed by the expression of the patient by demonstrating a thought about death and experience of worthlessness (Table 2).…”
Section: Execution Daymentioning
confidence: 96%
“…Subsequently, the execution of caning sentence for this case was performed to provide educational media for the society that views the execution. In contrast, a study has reported that although the local government of Aceh intended to implement the Islamic Sharia in to achieve a well-behaved society, the people who view the caning execution perceived it more as entertainment [11], rather than educational or deterring. Our assumption might have confirmed by the expression of the patient by demonstrating a thought about death and experience of worthlessness (Table 2).…”
Section: Execution Daymentioning
confidence: 96%
“…The penalties for perpetrators of sexual violence are considered lighter than those in the Criminal Code, which indicates the weakness of gender sensibility in the regulation. In addition, the application of caning for perpetrators based on the Qanun Jinayat has not only shifted to become a symbol for the local government's attention to the implementation of Islamic law but also to an arena for staging punishments for the community (Fadlia et al, 2020).…”
Section: B Qanun Jinayat and Aceh's Legal Pluralismmentioning
confidence: 99%